The concept ‘light from light’ in the Nicene creed: Is the metaphor still appropriate for Christian ethics today? - Vorster, Jacobus M. (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2026)
From a classic Reformed theological perspective,1 two questions arise when reflecting on the metaphor ‘light from light’ in the homoousios formulas of the Nicaeno-Constantinopolitanum of AD 381, especially within the domain of theological ethics. Firstly, what was the main classic interpretation of this metaphor; and secondly, is the metaphor still appropriate today considering the modern trend of ‘low’ Christologies as the key approach to Christian ethics? In these modern ‘low Christologies’, the divinity of Jesus and its relevance for theological ethics are questioned from the perspective of the ethics of immanent liberation rooted in the historical Jesus. In this article, the author reflects on these two questions. The central theoretical argument is that the classical understanding of the metaphor can enrich modern theological social ethics and broaden the concept of liberation into an all-encompassing vision of true humanity. To this end, the Greek and Latin texts of the Nicaeno-Constantinopolitanum are first presented with a modern English translation, followed by a brief explanation of the historical context of the Council of Nicaea. Contribution: The subsequent sections examine, with the Gnostic and Neo-Platonist roots of the metaphor, the biblical perspectives on Christ as the light of the world, and the relation between ‘low Christology’ and liberation ethics. In conclusion, the author ventures to indicate a way toward true humanity and moral agency flowing from the classic interpretation of the metaphor of the Son as ‘light from light’.